Epicardial and subcutaneous adipose tissue in Indigenous and non-Indigenous individuals: Implications for cardiometabolic diseases. Issue 1 (January 2020) - Sun, David F.; Kangaharan, Nadarajah; Costello, Benedict; Nicholls, Stephen J.; Emdin, Connor A.; Tse, Rexson; Gallagher, Celine; Kaur, Amrina; Roberts-Thomson, Kurt C.; Mahajan, Rajiv; Lau, Dennis H.; Sanders, Prashanthan; et al.
Abstract: Background: Obesity is prevalent in Indigenous populations who exhibit significant differences in body fat composition. While excess regional adiposity can be partially inferred from clinical measurements, noninvasive imaging allows for direct quantification of specific fat depots. Epicardial fat is a visceral adipose tissue that has been strongly associated with cardiometabolic disease in other populations. However, this ectopic fat depot has yet to be characterized in Indigenous populations. Methods: We studied 100 individuals matched for ethnicity (Indigenous Australian and Caucasian descent), age, gender, and body mass index. Epicardial and subcutaneous adipose tissue volumes was quantified with computed tomography. Associations of ethnicity and adiposity measures were assessed using linear regression. Results: Indigenous individuals had significantly greater epicardial fat volumes compared to non-Indigenous individuals (95.8 ± 37.5 vs 54.1 ± 27.6 cm 3, p < 0.001). In contrast, subcutaneous fat volumes were comparable in Indigenous compared to non-Indigenous individuals (22.1 ± 15.1 vs 20.3 ± 13.5 cm 3, p = 0.54). Sequential adjustment for age, gender, comorbidities, biochemical parameters, and medication use did not attenuate the association between Indigenous ethnicity and greater epicardial fat volume in multivariable models (B = 43.0, p < 0.001). Furthermore, this association did not materially change with the inclusion of various adiposity measures, such as body mass index, subcutaneous adipose tissue, or weight. Conclusions: Indigenous individuals have significantly greater epicardial fat, but similar subcutaneous fat volumes, compared to non-Indigenous individuals. This finding extends previous observations on body fat composition differences in these individuals, and supports the possibility that epicardial fat and other visceral adipose depots may be contributing to the greater burden of cardiovascular disease in Indigenous populations.